1981
DOI: 10.1115/1.3138294
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Compressional Behavior of Articular Cartilage and Its Associated Electromechanical Properties

Abstract: The compressive stiffness of articular cartilage was examined in oscillatory confined compression over a wide frequency range including high frequencies relevant to impact loading. Nonlinear behavior was found when the imposed sinusoidal compression amplitude exceeded a threshold value that depended on frequency. Linear behavior was attained only by suitable control of the compression amplitude. This was enabled by real time Fourier analysis of data which provided an accurate assessment of the extent of nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(77 citation statements)
references
References 0 publications
4
72
0
1
Order By: Relevance
“…In particular, based on earlier experimental results [24], we propose to use a power-law relation (14) where ξ(n r ) (units of force per area) and α(n r ) (unitless) are material properties that may vary along the directions n r . (For inhomogeneous materials, it is also possible to vary ξ and α spatially.)…”
Section: Fiber Constitutive Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, based on earlier experimental results [24], we propose to use a power-law relation (14) where ξ(n r ) (units of force per area) and α(n r ) (unitless) are material properties that may vary along the directions n r . (For inhomogeneous materials, it is also possible to vary ξ and α spatially.)…”
Section: Fiber Constitutive Relationmentioning
confidence: 99%
“…For example, the linear isotropic biphasic theory for soft hydrated tissues [13] can predict the transient response of cartilage deformation and interstitial fluid pressurization in confined compression creep, stress-relaxation, and dynamic loading [13][14][15][16], and indentation creep [17]. When accounting for the tension-compression nonlinearity arising from the fibrillar solid matrix, the biphasic theory can also predict the response of cartilage deformation and interstitial fluid pressurization in unconfined compression [3,4,7,11,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This finding reflects that the relative compressive energy dissipation of hyaline cartilage may be strongly dependent on the interstitial fluid flow at low frequencies. Lee et al examined the relationship between the compressive viscoelastic behavior and the streaming potential of articular cartilage (1) . They reported that the streaming potential of articular cartilage was induced by the flow of the electrolyte-containing interstitial fluid.…”
Section: Viscoelastic Properties Of Hyaline Cartilage (Articular Camentioning
confidence: 99%
“…The specimen was loaded in unconfined compression geometry between impermeable platens (1), (2) . The stress σ of the specimen was defined as the load normalized to the initial disk area, and the strain rate ε was referenced to the initial thickness.…”
Section: Dynamic Compression Testingmentioning
confidence: 99%
See 1 more Smart Citation